Evaluation and selection of promising soybean lines in diverse environments - Malek, MA; Monshi, FI; Rahman, L; Hakim, MA (Journal of the Bangladesh Agricultural University, 2011)
An experiment was conducted to evaluate the performance of eight selected soybean lines along with two check varieties in respect of maturity period, seed yield and yield contributing characters at five different locations during rabi season of 2007. Except number of seeds per pod, other yield contributing characters, seed yield and maturity period showed significant variations both in individual location and combined over locations. Among the lines and check varieties BAU-S/64 produced the highest number of branches per plant (4.7) while the check variety Sohag produced the lowest (2.8). Bangladesh soybean-4 produced the highest number of pods per plant (61). The seed yield of BAU-S/69 was the highest (2920 kg/ha) followed by BAU-S/64 (2721 kg/ha) while BAU-S/5 produced the lowest seed yield (2049 kg/ha). Among the five locations, the highest mean seed yield of 3167 kg/ha was produced at Chandpur followed by Mymensingh (2790 kg/ha) and Noakhali (2538 kg/ha). The lowest seed yield was recorded at Ishurdi (1363 kg/ha). Keywords: Soybean; Performance; Promising lines; Environments J. Bangladesh Agril. Univ. 8(2): 187–190, 2010 DOI: 10.3329/jbau.v8i2.7922